2015
DOI: 10.1371/journal.pone.0129039
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Toxicity of Ag Nanoparticles in Comparison to Bulk and Ionic Ag on Mussel Hemocytes and Gill Cells

Abstract: Silver nanoparticles (Ag NPs) are increasingly used in many products and are expected to end up in the aquatic environment. Mussels have been proposed as marine model species to evaluate NP toxicity in vitro. The objective of this work was to assess the mechanisms of toxicity of Ag NPs on mussel hemocytes and gill cells, in comparison to ionic and bulk Ag. Firstly, cytotoxicity of commercial and maltose stabilized Ag NPs was screened in parallel with the ionic and bulk forms at a wide range of concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 85 publications
6
83
0
9
Order By: Relevance
“…It is not known whether Ag acts directly on the transporter by binding to the substrate site or indirectly by blocking the ATPase activity or by acting on the membrane environment and thus causing conformational changes and affecting the transporter functionality. Ag NPs inhibit the Na + /K + -ATPase activity in the gills of zebrafish (Katuli et al, 2014), gill cells of mussels (Katsumiti et al, 2015) and rainbow trout (Schultz et al, 2012). However, addition of verapamil-HCl at the end of the Ag NP exposure in MDCKII-MDR1 and MDCKII-WT cells in our experiments led to an increase in the calcein accumulation reaching the verapamilHCl levels suggesting that the transporters are still functional (Fig.…”
Section: Mdckii-wtmentioning
confidence: 58%
See 1 more Smart Citation
“…It is not known whether Ag acts directly on the transporter by binding to the substrate site or indirectly by blocking the ATPase activity or by acting on the membrane environment and thus causing conformational changes and affecting the transporter functionality. Ag NPs inhibit the Na + /K + -ATPase activity in the gills of zebrafish (Katuli et al, 2014), gill cells of mussels (Katsumiti et al, 2015) and rainbow trout (Schultz et al, 2012). However, addition of verapamil-HCl at the end of the Ag NP exposure in MDCKII-MDR1 and MDCKII-WT cells in our experiments led to an increase in the calcein accumulation reaching the verapamilHCl levels suggesting that the transporters are still functional (Fig.…”
Section: Mdckii-wtmentioning
confidence: 58%
“…In addition to the NP-specific effects also Ag ions released from the NPs could contribute to the toxic effects (Gaiser et al, 2012;Griffitt et al, 2008;Kwok et al, 2012). An interference with the MXR mechanism has been recently shown for Ag NPs in mussel gill cells and hemocytes (Katsumiti et al, 2015). Given the important role of the MXR transporters as a defense mechanism and their broad substrate specificity, the predicted environmental release of Ag NPs and the high affinity of Ag for proteins, a better understanding of this topic is required.…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…The mechanism of silver genotoxicity mostly depends on the oxidative stress, the activation of lysosomal acid phosphatase activity and disruption of actin cytoskeleton, but effects mainly expressed for ionic silver impact. 16 The results of this study showed high level of direct genotoxic action of silver nitrate (Figure 2). That is why it is an important task to produce soluble silver compounds with low toxicity.…”
Section: Discussionmentioning
confidence: 60%
“…Single colonies from the grown plate were transferred into 4 mL of Nutrient brothand incubated overnight at 30°C. A centrifugation procedure at 3000 rpm for 15 …”
Section: Antifungal Testmentioning
confidence: 99%
“…12 Moreover exploring the mechanical effect of composite resin modified by ZnO NPs determined increasing compressive and shear without altering the flexural strength of composite resin, 13 from the other hand toxicity of Ag NPs to human cell and brown dicoloration of PMMA result in suspecting the use of this material any more. [14][15][16] Overall, Lower toxicity of ZnO NPs, their killing ability of C. albicans, white appearance and ability to reinforce of composite resin is some advantages of this material. As a result of these reasons and due to the fact that the addition of ZnO NPs to PMMA used in making a denture base is yet to be examined, the present study was carried out to evaluate the antifungal properties of ZnO NPs in acrylic resin and comparison with Ag NPs.…”
Section: Introductionmentioning
confidence: 99%